2011
DOI: 10.3899/jrheum.110425
|View full text |Cite
|
Sign up to set email alerts
|

The OMERACT Ultrasound Task Force — Status and Perspectives

Abstract: This article reports the most recent work of the Outcome Measures in Rheumatology (OMERACT) Ultrasound Task Force, and highlights the future research priorities discussed at the OMERACT 10 meeting. Results of the following studies were presented: (1) intra- and interobserver reliability of ultrasound detecting and scoring synovitis in different joints of patients with rheumatoid arthritis (RA); (2) systematic review of previous ultrasound scoring systems of synovitis in RA; (3) enthesitis systematic review and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
69
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 106 publications
(74 citation statements)
references
References 19 publications
3
69
0
2
Order By: Relevance
“…The need for many steps in the development of these definitions emphasizes the lack of validation in the US assessment of pediatric joints, which are subject to great variability (2). Previous work done in adults by the OMERACT Ultrasound Group has shown that even assessments of single types of joints can be challenging and might need a relatively lengthy development process of precise definitions in order to achieve good intra-and interrater reliability of this method (14). Our study focused on the structures of the healthy joint but was restricted to the main structures of the diarthrodial joint.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The need for many steps in the development of these definitions emphasizes the lack of validation in the US assessment of pediatric joints, which are subject to great variability (2). Previous work done in adults by the OMERACT Ultrasound Group has shown that even assessments of single types of joints can be challenging and might need a relatively lengthy development process of precise definitions in order to achieve good intra-and interrater reliability of this method (14). Our study focused on the structures of the healthy joint but was restricted to the main structures of the diarthrodial joint.…”
Section: Discussionmentioning
confidence: 99%
“…Given the lack of definitions for normal sonoanatomy as well as synovitis in children (2), a task force for pediatric US was established within the Outcome Measures in Rheumatology (OMERACT) Ultrasound Group to start the essential process of standardization of US assessment in children. Standardization, including precise definitions for US findings, has been shown in adults to be essential for good interrater reliability (14). In order to reflect the variability of relevant anatomy according to age and maturity in children, a decision was taken to start with definitions of the components of the healthy joint first.…”
Section: Significance and Innovationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the different applications of MSUS fields of validation, the pediatric field has been considered as one of the main areas. With the aim of improving the validity of MSUS for the diagnosis and management of synovitis in juvenile idiopathic arthritis (JIA), a new subtask force was included (4). This task force has developed a stepwise process: first, the development and validation, using the Delphi process, of definitions for US findings in healthy children and patients with JIA, and second, creating a consensus agreement on a precise scanning method in different age groups, with the collection of images showing the sonographic appearance of blood vessels in several joints, to be included in an atlas format.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, the OMERACT MSUS group has assessed the metric properties of US in detecting and scoring potential endpoint in rheumatic diseases for clinical trials and practice [24][25][26][27][28]. The group has worked on validation of US-detected and graded tendon damage in RA [19,20], which is an essential component of the structural damage in this disease [19,20].…”
Section: Discussionmentioning
confidence: 99%